Constructing compatible interface between Li7La3Zr2O12 solid electrolyte and LiCoO2 cathode for stable cycling performances at 4.5 V. Issue 16 (20th April 2021) - Dong, Yuwan; Su, Panzhe; He, Guanjie; Zhao, Huiling; Bai, Ying
Abstract : A compatible interface between Li7 La3 Zr2 O12 and LCoO2 has been constructed through a facile surface modification strategy, which significantly improves the cycling stability of LCoO2 cathode material at a high cut-off voltage of 4.5 V. Abstract : With high theoretical capacity and tap density, LiCoO2 (LCO) cathode has been extensively utilized in lithium-ion batteries (LIBs) for energy storage devices. However, the bottleneck of structural and interfacial instabilities upon cycling severely restricts its practical application at high cut-off voltage. From another perspective, the compatibility between the electrode and electrolyte is highly valued in the development of all-solid-state batteries. Herein, we construct a compatible interface between Li7 La3 Zr2 O12 (LLZO) and LCO through a facile surface modification strategy, which significantly improves the cycling stability of LCO at a high cut-off voltage of 4.5 V. Characterization results demonstrate that the LCO@1.0 LLZO sample delivers a desirable capacity retention of 76.8% even after 1000 cycles at 3.0–4.5 V with the current density of 1 C (1 C = 274 mA g −1 ). Further investigation indicates that the LLZO modification layer could protect the LCO electrode through effectively alleviating the side reactions, which not only facilitates the Li + transportation at the interface but also mitigates the bulk structure degradation. Moreover, it is also established that a small amount of La and Zr ions could gradiently migrate into the surface lattice of LCO to generate a thin layer of the surface solid solution Li–Co–La–Zr–O. Thus formed pinning region between surface modified LLZO and LCO cathode could contribute both to their mechanical compatibility and Li + kinetics behavior upon repeated cycling. This work not only provides a strategy in broadening the operation potential and extracting higher capacity of LCO but also sheds light on constructing compatible interfaces in LIBs, especially for all-solid-state energy storage and conversion devices.